1993
DOI: 10.1021/es00041a006
|View full text |Cite
|
Sign up to set email alerts
|

Development of an improved image processing based visibility model

Abstract: An image processing based visibility model is presented in which model calculations are displayed as synthetic color photographs that have the appearance of a smog event. A theoretically based model for light scattering and absorption in a plane parallel atmosphere is used to determine sky color and to provide accurate prediction of skylight addition to the line of sight between the observer and objects in the field of view. Data for testing the visibility model are collected experimentally, including standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
8

Year Published

1996
1996
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 13 publications
1
27
0
8
Order By: Relevance
“…Contrast transmittance: Photographs and time-lapse film 189,191,198,[246][247][248][249][250] Particle scattering (b scat,p ):…”
Section: -244mentioning
confidence: 99%
“…Contrast transmittance: Photographs and time-lapse film 189,191,198,[246][247][248][249][250] Particle scattering (b scat,p ):…”
Section: -244mentioning
confidence: 99%
“…The complex mixture of chemical substances present in particles of a given size is then represented as an external mixture of the appropriate number of distinctly different particle types. The method of calculating refractive indices and light scattering that is described in this paper has been discussed previously by Larson et al [1988] and Eldering et al [1994, 1993]. Eldering et al [1993] demonstrated that skylight radiances calculated by these methods compare well to those measured independently with a radiometer.…”
Section: Model Descriptionmentioning
confidence: 99%
“…image processing-based visibility models[Eldering et al, 1993] that can produce synthetic color photographs of the appearance of the surrounding landscape as it would be seen from inside the air parcel in those cases where the visual range Lv is comparable to the dimensions of the air parcels tracked by a trajectory model (i.e., when Lv is less than or equal to several kilometers).…”
mentioning
confidence: 99%